IDENTIFICATION OF A MAJOR QUANTITATIVE TRAIT LOCUS CONFERRING RICE BLAST RESISTANCE USING RECOMBINANT INBRED LINES - Sobrizal Sobrizal; Masdiar Bustamam; Carkum Carkum; Ahmad Warsun; Soeranto Human; Yoshimichi Fukuta (Indonesian Agency for Agricultural Research and Development, 2010)
Blast disease caused by Pyricularia oryzae is one of the limiting factors for rice production world wide. The use of resistant varieties for managing blast disease is considered as the most eco-friendly approaches. However, their resistances may be broken down within a few years due to the appearance of new virulent blast races in the field. The objective of the present study was to identify the quantitative trait locus (QTL) conferring resistance to blast disease using 126 recombinant inbred (RI) lines originated from a crossing of a durably resistant upland rice genotype (Laka) and a highly susceptible rice accession cultivar (Kencana Bali). The RI population was developed through a single seed descent method from 1997 to 2004. Resistance of the RI lines was evaluated for blast in an endemic area of Sukabumi, West Java, in 2005. Disease intensity of the blast was examined following the standard evaluation system developed by the International Rice Research Institute (IRRI). At the same year the RI lines were analyzed with 134 DNA markers. Results of the study showed that one major QTL was found to be associated with blast resistance, and this QTL was located near RM2136 marker on the long arm of chromosome 11. This QTL explained 87% of the phenotypic variation with 37% additive effect. The map position of this QTL differed from that of a partial resistant gene, Pi34, identified previously on chromosome 11 in the Japanese durably resistant variety, Chubu 32. The QTL, however, was almost at the same position as that of the multiple allele-resistant gene, Pik. Therefore, an allelic test should be conducted to clarify the allelic relationship between QTL identified in this study and the Pik. The RI lines are the permanent segregating population that could be very useful for analysing phenotypic variations of important agronomic traits possibly owned by the RI lines. The major QTL identified in this study could be used as a genetic resource in improvement of rice varieties for blast resistance in Indonesia